Synthesis of oxygenated fuel additives via glycerol esterification with acetic acid over bio-derived carbon catalyst. (1st December 2017) - Okoye, P.U.; Abdullah, A.Z.; Hameed, B.H.
Graphical abstract: Highlights: Crude glycerol serves as a carbon precursor for heterogeneous acid catalyst synthesis. Synthesis method involved partial sulphonation and carbonization in one step. The catalyst was utilized to synthesized oxygenated fuel-additives from glycerol. Seven times reusability was achieved without catalyst deactivation. Abstract: Glycerol derived from biodiesel (BD) production is oversupplied and requires urgent utilization. Hence, crude bio-derived glycerol was utilized as a carbon precursor for heterogeneous solid acid catalyst synthesis via partial sulphonation and carbonization in a single step. The as-synthesized catalyst was utilized to catalyze glycerol acetylation reaction with acetic acid to produce oxygenated fuel additives (diacetin and triacetin) and monoacetin. Under reaction conditions of 110 °C, glycerol-to-acetic acid molar ratio of 3, 2 wt% catalyst dose, and 3 h reaction time, 88% combined DAG and TAG selectivity was attained with a corresponding glycerol conversion of 99%. The high surface acid sites density of the catalyst primarily contributed to its enhanced catalytic performance. The catalyst displayed sufficient heterogeneity and robustness in polar reaction media despite high hydrophilic acid sites density. Hence, it was reused in seven cycles of the experiment without experiencing significant deactivation.